2 fabric appliqué quilts [videorecording (DVD)] / with Nancy Lee Chong. - Chong, Nancy Lee (Pacific Rim Quilt Co., 2005)
"With this video you will learn Nancy's stress-free approach to needleturn appliqué while making your 2 FAQ quilt."--Container.